2021
DOI: 10.1210/endrev/bnab036
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Manifestations and New Developments in Mitochondrial Disease

Abstract: Mitochondrial diseases are a group of common inherited diseases causing disruption of oxidative phosphorylation. Some patients with mitochondrial disease have endocrine manifestations, with diabetes being predominant but also include hypogonadism, hypoadrenalism and hypoparathyroidism. There have been major developments in mitochondrial disease over the last decade that have major implications for all patients. The collection of large cohorts of patients has better defined the phenotype of mitochondrial diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 190 publications
(233 reference statements)
0
15
0
6
Order By: Relevance
“…Certain mtDNA depletion syndromes may present with hepatocerebral syndrome causing hypoglycemia with hepatic and neurologic abnormalities, re ected by abnormal liver transaminases and coagulation studies [3]. Growth hormone de ciencies have mostly been reported as a factor in the development of short stature in patients with MTDs, as seen in our patient [8].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Certain mtDNA depletion syndromes may present with hepatocerebral syndrome causing hypoglycemia with hepatic and neurologic abnormalities, re ected by abnormal liver transaminases and coagulation studies [3]. Growth hormone de ciencies have mostly been reported as a factor in the development of short stature in patients with MTDs, as seen in our patient [8].…”
Section: Discussionmentioning
confidence: 82%
“…The endocrine system is commonly affected, predominantly manifesting as diabetes mellitus as well as hypogonadism, hypoadrenalism, and hypoparathyroidism [3]. A 2019 study found that on chart review, non-diabetic patients with MTD had signi cantly increased rates of hypoglycemic episodes compared to the general population [4], although this complication is not well studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This man’s height is 1.75 m (body mass index 26.1 kg/m 2 ), which would be unusual for people with classical type 2 diabetes. Interestingly, people with m.3243A>G-associated maternally inherited diabetes and deafness are invariably lean at presentation 3…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, hormone levels strongly influence BP values. As MIDs frequently manifest with endocrine involvement [4], it is crucial to know how many of the included patients had endocrine disturbances.…”
mentioning
confidence: 99%